It is time to fix the low financing trap: public spending on education revisited - Keith M. Lewin (Emerald Publishing, 2023)
Purpose - This paper aims to explore whether there is a "low financing trap" that results in underfunding of education systems in low and lower middle income countries (LICs and LMICs). It shows public investment in education has not increased over the last two decades despite extensive advocacy and has equilibrated at about 4% of GDP. More than 6% of GDP is needed to achieve the sustainable development goals. Design/methodology/approach - This research uses large scale data from the UNESCO Institute of Statistics and the World Bank to analyse patterns of investment across sub-Saharan Africa. The most recent data downloaded in 2022 are used for each country. The analysis uses time series analysis to show how flows of resources for education have evolved and illustrates the limits to growth. Findings - The research develops a taxonomy of countries and identifies three bands of effort for investment in education. Individual countries tend to remain in the same band of expenditure level and only the highest band countries are likely to be able to finance their development goals from their own resources between now and 2030. Escape from the low financing trap is critical for future educational development. Originality/value - Innovative approaches to external assistance are needed which recognise that domestic revenues are at the heart of sustainable financing and that greater efficiency and effectiveness are critical to sustainable solutions. The priority is to accelerate the development of fiscal states, which can finance public goods from domestic revenue and make good use of concessionary assistance.